2017
DOI: 10.1097/qad.0000000000001452
|View full text |Cite|
|
Sign up to set email alerts
|

Acceptability and use of a dapivirine vaginal ring in a phase III trial

Abstract: Background The MTN-020/ASPIRE trial evaluated the safety and effectiveness of the dapivirine vaginal ring for prevention of HIV-1 infection among African women. A nested qualitative component was conducted at six of 15 study sites in Uganda, Malawi, Zimbabwe and South Africa to evaluate acceptability of and adherence to the ring. Method Qualitative study participants (n = 214) were interviewed with one of three modalities: single in-depth interview, up to three serial interviews or an exit Focus Group Discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 34 publications
6
96
0
Order By: Relevance
“…Nevertheless, biomarkers of adherence and qualitative data indicate that some women do not consistently use the ring, in particular young women. Consistent with previous trials of candidate microbicide gels and cervical barriers, ring nonadherence may have been caused by various contextual reasons such as perceived interference with sex, menses, short-term periods of abstinence and nondisclosure to male partners [9][10][11][12][13][14]. As with oral PrEP, and other antiretroviral-based approaches in development, use of a licensed dapivirine ring would require regular clinic visits and monitoring.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, biomarkers of adherence and qualitative data indicate that some women do not consistently use the ring, in particular young women. Consistent with previous trials of candidate microbicide gels and cervical barriers, ring nonadherence may have been caused by various contextual reasons such as perceived interference with sex, menses, short-term periods of abstinence and nondisclosure to male partners [9][10][11][12][13][14]. As with oral PrEP, and other antiretroviral-based approaches in development, use of a licensed dapivirine ring would require regular clinic visits and monitoring.…”
Section: Introductionmentioning
confidence: 78%
“…Although this study was not designed to measure a specific behavioural framework, the observed trajectory is reflective of a stages of change model , which describes behavioural transitions from knowledge to action; and models based on the theory of diffusion of innovations which similarly describe the process through which new innovations, such as these novel vaginal products, are accepted at a societal level. Research with participants from clinical trials of the dapivirine ring has highlighted that this novel technology required several months of use to build comfort and to dispel fears and concerns . Peer and research staff support were critical for overcoming this early adoption period.…”
Section: Discussionmentioning
confidence: 99%
“…Women were also instructed to use condoms during the trial. Qualitative data were collected in a nested qualitative component in each of the four study countries (Malawi, South Africa, Uganda, Zimbabwe) at a total of six sites that were located in a range of rural, urban and suburban settings [2]. Qualitative participants (n = 214) were enrolled into a single in-depth interview (IDI) (n = 34), 3 serial IDIs (n = 80), or an exit focus group discussion (FGD) (n = 100).…”
Section: Methodsmentioning
confidence: 99%
“…Using semi-structured interview guides administered in English or local languages, all interviews were audio-recorded, transcribed, translated, coded, and analyzed. Participants also completed Audio Computer Assisted Self-Interviews (ACASIs) at month 3 and final visits which included questions about experiences with the ring during sex [2]. …”
Section: Methodsmentioning
confidence: 99%
“…27 Salient findings showed first that although participants initially feared use of the vaginal ring, they grew to like it and had a sense of ownership and ease of use over time. Second, support by staff and their peers aided in the uptake and sustained use of the ring.…”
Section: Discussionmentioning
confidence: 99%